Ecology And The Environment - Time-Life Books (Time-Life Books : Hong Kong, 1994)
A visually engaging encyclopedia volume exploring key topics in ecology and environmental science, including: Ecosystems, biodiversity, food webs, habitats Pollution, conservation efforts, global environmental challenges Illustrated with photographs, diagrams, and explanatory text aimed at general readers and students.
Keywords: Environmental science